PENGELOMPOKAN KABUPATEN/KOTA BERDASARKAN KOMODITAS PERTANIAN MENGGUNAKAN METODE K MEDOIDS - Wuryandari, Triastuti; Rusgiyono, Agus; Setyowati, Etik (MEDIA STATISTIKA, 2016)
The land in Central Java have a lot of nutrients, so considered suitable for agriculture. North Central Java and some areas in Central Java suitable agriculture for food crops of rice and other crops such as corn, soybeans, peanuts, sweet potatoes and cassava. With the diversity of agricultural production of food crops in Central Java it is necessary to facilitate the grouping of government in determining the specific policy in agriculture in order to achieve national food security. These grouping using cluster analysis with non hierarchical partitioning methode k medoids. The cluster using a point value from the agricultural commodity crops, thereby reducing the sensitivity of the data outliers. Keywords: Central Java, Agricultural Commodities, Cluster Analysis, Non-Hierarchical,     k Medoids, Outlier